Revising Cognitive and Evolutionary Science of Religion: Religion as an Adaptation - Szocik, Konrad (New Approaches to the Scientific Study of Religion, 2021)
Introduction -- Chapter1. Cognitive approach to the study of religion: basic concepts and theories -- Chapter2. Adaptationist account and pragmatic usefulness of religion -- Chapter3. Content biases versus context biases and the critique of intuitiveness and naturalness of religion -- Chapter4. Religion and biological evolution: what is right and what is wrong in Darwinian approach to the study of religion -- Chapter5. Religion and cultural evolution. Does supernatural punishment matter for evolution of altruism and cooperation? -- Chapter6. The challenge of atheism and non-belief for cognitive and evolutionary approach -- Chapter7. Why adaptationist account is better than cognitive one but both of them do not provide sufficient explanatory frameworks to explain religion -- Conclusion.